2021
DOI: 10.1177/23259671211046929
|View full text |Cite
|
Sign up to set email alerts
|

Double-Layered Quadriceps Tendon Autografts Provide Lower Failure Rates and Improved Clinical Results Compared With Hamstring Tendon Grafts in Revision ACL Reconstruction

Abstract: Background: We developed a quadriceps-tendon graft technique using a double-layered, partial-thickness, soft tissue quadriceps tendon graft (dlQUAD) for anterior cruciate ligament reconstruction (ACLR). This technique allows simple femoral loop button fixation and a limited harvest depth of the quadriceps tendon. Purpose: To evaluate the outcome of patients undergoing revision ACLR using the dlQUAD technique compared with a hamstring tendon graft (HT). Study Design: Cohort study; Level of evidence, 3. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 40 publications
(61 reference statements)
0
28
0
1
Order By: Relevance
“…Nine studies met inclusion criteria for this systematic review with a total patient population of 606, including 349 QT, 169 HT, and 88 BTB RACLR (Fig. 1) [3, 6, 12, 15, 20, 26, 39, 43, 60]. Average follow‐up ranged from 24 to 52.3 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies met inclusion criteria for this systematic review with a total patient population of 606, including 349 QT, 169 HT, and 88 BTB RACLR (Fig. 1) [3, 6, 12, 15, 20, 26, 39, 43, 60]. Average follow‐up ranged from 24 to 52.3 months.…”
Section: Resultsmentioning
confidence: 99%
“…Side‐to‐side differences (STSD) measured by KT‐1000, KT‐2000, or Rolimeter arthrometers were reported in 6/9 studies [3, 12, 15, 20, 26, 43]. The mean weighted STSD was 1.7 mm (SD = 0.6) and 2.1 mm (SD = 0.5) for QT and HT, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Previous studies found similar functional outcomes with QT and HT autografts for revision reconstruction. 2,13 Another study 7 reported improved functional outcomes with QT compared with HT autograft in revision ACL reconstruction. Hunnicutt et al 16 demonstrated significant improvement in functional outcomes from the preoperative to postoperative period with QT autograft in revision ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both techniques resulted in good to excellent clinical outcome as compared with related studies. 2,5,6,9 A recent systematic review reported a mean Lysholm score of 88.9, a subjective International Knee Documentation Committee score of 83.3, and a Knee injury and Osteoarthritis Outcome Score of 68.3 for Sport/Recreation at final midterm follow-up. 9 However, it is known that by first-time revision ACLR the outcome critically depends on concomitant injuries, patient age, sporting demands, and follow-up, which compromises this comparison.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%